The impact of democracy on economic growth in sub-Saharan Africa, 1982 - 2012 - Takaaki Masaki; Nicolas Van de Walle (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Does democracy promote economic growth? There is still an ongoing debate over the economic implications of democracy, and this question has gained critical importance particularly in the African context, where a wave of democratization in the early 1990s coincided with the start of a new era of rapid economic growth. In this paper, we revisit this important topic and argue that the existing literature is inadequate in distinguishing the effects of regime transitions and democratic consolidation on economic growth. Through the analysis of the latest economic and political data, which include up to 43 countries in sub-Saharan Africa for the period of 1982 - 2012, we find strong evidence that democracy is positively associated with economic growth, and that this 'democratic advantage' is more pronounced for those African countries that have remained democratic for longer periods of time. Our findings call for more nuanced studies that carefully distinguish potentially divergent effects of regime transitions and democratic consolidation on economic growth.
Keywords: O10; O40; O43; O57; 330; economic growth; democracy; democratization